Importance of phosphate pock application for sustaining agricultural production in Egypt - Hellal, F. (2021)
In Egypt, the natural phosphate rock is located in Sebaiya (Nile Valley), Safaga (Red Sea), and Abu Tartur (Western Desert). The higher the organic matter contents in soil, the better dissolution of the PR. Legumes are particularly suited for the use of PR. Biological solubilization of phosphate rock is more environmentally friendly than acidulation. Fungi are widely used as producers of organic acids, and particularly, some Aspergillus and Penicillium species have been directly introduced into the soil in order to solubilize the phosphate rock. Biological solubilization will make phosphorous available for plant use with minimum pollution to the environment. Phosphate rock inoculated with bacteria and Mycrrohizae proved to be a suitable approach to use PR for continuous crop production.